Radio Channel Model of Wireless Sensor Networks Operating in 2.4 GHz ISM Band - Giacomin, João C.; Correia, Luiz H. A.; Heimfarth, Tales; Pereira, Geraldo M.; Silva, Vinicius F.; de Santana, Joao L. P. (INFOCOMP Journal of Computer Science, 2010)
This paper presents a novel signal propagation model of wireless sensor network (WSN) for outdoor open environments. This model can be used in simulators and also in WSN services as localization discovery. The model here proposed produces results with higher accuracy when compared to the models existing in the literature. It is based on the existing double path propagation model (tworay), but differently from the previous works, it takes into account the directivity of the antennas and the variable reflectivity index of the soil. Experiments confirmed the outstanding results of our propagation model